Empirical referents of professionals` emotional safety - Lazorko , Olha; Shevtsova, Tetiana (Psychological Prospects Journal, 2020)
Purpose. The article proposes to determine the place of emotional safety in the structure of professional security of the individual, as well as empirical reviewers of emotional safety. An important task is to identify the links between the general emotional background and the tendency to stress with self-esteem and burnout on three scales: emotional exhaustion, depersonalization and reduction of personal achievements; we assume that the emotional safety of the individual is related to the specifics of professional activities: working with people or with documents, management activities.Methods. In order to study the psychological features of the manifestation of emotional safety of the individual, including such empirical referents as stress, emotional exhaustion, depersonalization, reduction of professional achievements, expression of basic emotions and self-esteem, we used the following psychodiagnostic techniques: "Determining the degree of stress" by E. Tarasov); "Professional burnout" (by K. Maslach, S. Jackson in the adaptation of E. Vodopyanova); "Scale of differential emotions" (according to K. Izard); "Determining the level of self-esteem" (according to G. Kazantseva).Results. The emotional safety of a professional is seen as a sense of confidence in possession of internal psychological resources to confront the threats and dangers associated with professional activities. On the one hand, the emotional safety of a professional is supported by internal psychological resources, and on the other hand, a safe environment and trust in the organization. The propensity to stress, emotional background, level of burnout and self-esteem can hypothetically be the empirical referents that will identify the presence or absence of these resources. The results of a study aimed at examining the relationship between stress propensity and general emotional background with the level of self-esteem and burnout are presented. It is proved that the state of emotional safety is associated not so much with the psychological characteristics of the subjects, but with the specifics of the leading professional activity: working with documents, working with people, mixed form (people and documents), as well as leadership.Conclusions. There are significant statistical relationships between indicators of basic emotions and indicators of burnout (emotional exhaustion, depersonalization, reduction of professional achievements) and the level of self-esteem and between indicators of burnout and stress and self-esteem of employees. Further study of the phenomenon of emotional safety of the professional's personality is seen in the context of the organizational environment and interpersonal interaction of the organization's staff. An important task and challenge for organizational psychologists today is to find useful tools and programs to ensure the emotional stability and safety of staff in the workplace, which is certainly a promising area of further research.
Keywords: personal safety; professional activity; propensity to stress; self-esteem; basic emotions; professional burnout